Media Digital Book: Inovasi Proses Peningkatan Keterampilan Membaca Bahasa Arab Siswa MTs Maarif Selomerto Wonosobo Masa Pandemi - Nuur Laila Luthfiyah; Lilik Rochmad Nurcholisho; Rifqi Aulia Rahman (Armala, 2022)
This research departs from the eternal problem that media innovation as an intermediary for the transfer of teaching materials is not effective and efficient in improving students' skills. This study aims to determine the use of digital books in improving reading skills. This study uses field research with a quantitative approach and with the type of experimental research. While the research design is a pretest-post-test Control Group Design in practice which is carried out at MTs Ma'arif Selomerto. Methods of data collection is done by observation, interviews, documentation and tests. The results of this study indicate an increase in reading skills in the experimental class by 0.598. 2) the results of hypothesis testing show the level of error. and for the 1% stage, we get dk = (22+20)-2= 40, we get ttable 2.704. And for the 5% error stage, we get dk = (22+20)-2= 40, we get ttable 2.021. In short, there is a significant difference in improving Arabic reading skills for class IX MTs Ma'arif Selomerto who use digital book media and those who do not use digital book media.